METABOLIC SYNDROME PREVALENCE IN RUSSIAN CITIES - O. P. Rotar; R. A. Libis; E. N. Isaeva; A. M. Erina; D. A. Shavshin; E. V. Moguchaya; E. P. Kolesova; M. A. Boyarinova; N. V. Moroshkina; O. I. Yakovleva; V. N. Solntsev; A. O. Konradi; et al. (Российский кардиологический журнал)
Aim. Metabolic syndrome (MS) is a combination of the key cardiovascular risk factors, namely obesity, carbohydrate metabolism disturbances, arterial hypertension (AH), and dyslipidemia. MS prevalence varies, depending on the MS definition used. The aim of this study was to assess the prevalence of MS and its components in large Russian cities (St. Petersburg, Kursk, Orenburg, and Kaliningrad), using international MS criteria. Material and methods. In total, 1046 individuals were screened in 4 cities: 309 in St. Petersburg, 170 in Kursk, 279 in Orenburg, and 288 in Kaliningrad. All participants underwent a questionnaire survey on demographics, risk factors, lifestyle, family history, comorbidities and treatment. Blood pressure measurement (3 measurements on the right arm) and anthropometry were also performed. Lipid profile and fasting glucose levels were measured with the use of Hitachi-902 analyser (Roche Diagnostics). MS was diagnosed based on the criteria by ATP III (2001–2005), IDF (2005), and JIS (2009). Results. High prevalence of MS was observed regardless of the criteria used; the highest prevalence was registered for the JIS-2009 criteria. For all MS criteria, no significant difference in MS prevalence was registered across the cities, or between men and women in each city. The majority of the patients (over 80%, regardless of the criteria used) had at least one MS component, with the highest prevalence observed in Kursk (94% for IDF-2005 and JIS-2009 criteria). Conclusion. In each region, the prevalence of MS was high, which might be related to high levels of cardiovascular morbidity and mortality in Russia. The IDF-2005 criteria agreed with the JIS-2009 ones to a greater extent than with the ATP III definition. However, prospective studies are needed to establish the national normal values of waist circumference, for reliable diagnostics of abdominal obesity in the Russian population.